Can heart failure phenotypes be predicted by cardiac remodelling peripartum or postpartum? - Agarwal, Megha; Leeson, Paul; Kitt, Jamie (Frontiers in Cardiovascular Medicine, 2024)
Hypertension during pregnancy affects up to 10% of pregnancies and is associated with significant cardiovascular morbidity and mortality. In the short-term it can result in pre-eclampsia, haemolysis, elevated liver enzymes and low platelets (HELLP) syndrome, or even hypertension associated acute heart failure, all of which may necessitate pre-term delivery to prevent maternal or neonatal death. In the long term, a history of gestational hypertension and pre-eclampsia significantly increases the risk of future cardiovascular disease including chronic hypertension, coronary artery disease, heart failure and stroke. This review explores our current level of knowledge of the phenotypes of heart failure, paying particular attention to those specific to women, and the role of pregnancy and non-pregnancy related risk factors in the development of this condition. We discuss why women with hypertensive pregnancy may be disproportionately affected by heart failure with preserved ejection fraction (HFpEF) and whether a unique phenotype of heart failure unique to hypertensive pregnancy exists. Finally, we explore how future cardiovascular risk may be predicted based on cardiac remodelling during or after pregnancy and suggest potential areas of further research in the field.